STUDI LITERATUR ISLAMIC FINTECH - Afrizal, Afrizal (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to analyze the development of Islamic fintech and its role in Islamic finance from various literatures, especially journal articles of international repute and indexed by Scopus. This research is a type of qualitative-descriptive research with a literature study approach. The literature study was carried out by collecting journal articles that were in accordance with the research objectives using the Publish or Perish (PoP) application, then content analysis was carried out. Content analysis is an analytical method by trying to find out the content and intent of a text to produce an objective description. The results of the study show several findings, namely: first, the research topic is divided into three main topics, namely first, market analysis on what factors influence a customer to use or not use fintech, second, the impact of fintech on the economy, and third, fintech implementation. in various fields of the economy.